Non-contact imaging of pipe thinning using elastic guided waves generated and detected by lasers. (June 2017) - Hayashi, Takahiro
Abstract: Defect images in a plate can be obtained by the generation and detection of flexural elastic waves using a pulsed laser and a laser Doppler vibrometer. The author has developed an experimental system—called an E-camera—that establishes extremely fast imaging. This paper describes the application of the E-camera to imaging of pipe thinning. The first experiments using a straight pipe revealed that resonance patterns appear significantly at certain frequencies due to guided waves propagating both in the longitudinal and circumferential directions, which is a unique characteristic of pipe structures. A pipe thinning located at various circumferential positions could also be visualized appropriately. Moreover, pipe thinning was successfully detected in both straight and branch pipes located at a distance of 6.0 m from the E-camera system. Highlights: Non-contact defect imaging system was applied to inspection of pipe thinning. Circumferential resonance patterns were obtained at the cut-off frequencies. A pipe thinning was visualized appropriately for straight and branch pipes.